Journal of Institute of Science and Technology: A Strong Foundation in Basic Sciences - Sharma, Chhatra Mani; Ghimire, Madhav Prasad; Pandey, Kishor; Pokharel, Binod; Neupane, Bhanu Bhakta; Kafle, Jeevan (Journal of Institute of Science and Technology, 2025)
EDITORIAL Over the last four years, the Journal of Institute of Science and Technology (JIST) has seen remarkable growth in the diversity of its scientific contributions. A notable trend in this period has been the substantial presence of research rooted in the basic sciences—physics, chemistry, and biology—which have accounted for 52% of all published articles. This consistent emphasis reflects not only the vitality of foundational disciplines but also their indispensable role in shaping applied innovations. Basic sciences are the foundations upon which technological progress and interdisciplinary exploration are built. In an era increasingly driven by applications in artificial intelligence, climate resilience, biotechnology, and material sciences, it is essential to remember that each of these advances stands on decades of rigorous basic research. By publishing a majority of works from these core domains, JIST has reaffirmed its commitment to nurturing scientific inquiry at its most fundamental level. We commend our contributing authors, reviewers, and editorial team for maintaining high standards in these disciplines. The high proportion of basic science articles is also a reflection of the strong research culture in our associated institutions and the growing global recognition of JIST as a credible platform for theoretical and experimental research. As we look to the future, we aim to maintain this balance while encouraging interdisciplinary submissions that connect basic science with other disciplines. We believe that fostering such integration will not only advance knowledge but also address some of the most pressing challenges of our time. In conclusion, the past four years have underscored the journal’s role as a custodian of core scientific values. We are proud of this trajectory and look forward to further strengthening the scientific dialogue that begins in the laboratory but resonates far beyond it. Chief Editor: Prof. Chhatra Mani Sharma, PhD Editors: Madhav Prasad Ghimire, PhD Kishor Pandey, PhD Binod Pokharel, PhD Bhanu Bhakta Neupane, PhD Jeevan Kafle, PhD